2011
DOI: 10.1029/2010ja015874
|View full text |Cite
|
Sign up to set email alerts
|

Midnight sector observations of auroral omega bands

Abstract: [1] We present observations of auroral omega bands on 28 September 2009. Although generally associated with the substorm recovery phase and typically observed in the morning sector, the features presented here occurred just after expansion phase onset and were observed in the midnight sector, dawnward of the onset region. An all-sky imager located in northeastern Iceland revealed that the omega bands were ∼150 × 200 km in size and propagated eastward at ∼0.4 km s −1 while a colocated ground magnetometer record… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
32
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(42 citation statements)
references
References 55 publications
7
32
3
Order By: Relevance
“…With the T96 model we can indeed map the flow shears to this downtail region (Table S1). This region is close to the previously suggested source region of omega bands (Jorgensen et al, ; Wild et al, ). Therefore, it is unlikely that the shear is between the plasma sheet flow and the LLBL flow, because LLBL flow is not expected to penetrate to the inner edge of the plasma sheet.…”
Section: Summary and Discussioncontrasting
confidence: 97%
“…With the T96 model we can indeed map the flow shears to this downtail region (Table S1). This region is close to the previously suggested source region of omega bands (Jorgensen et al, ; Wild et al, ). Therefore, it is unlikely that the shear is between the plasma sheet flow and the LLBL flow, because LLBL flow is not expected to penetrate to the inner edge of the plasma sheet.…”
Section: Summary and Discussioncontrasting
confidence: 97%
“…The combined upward and downward current regions covered less than 1 MLT which corresponds to 560 km in the ionosphere at 70° ILAT, with the upward current regions covering between 80 km and 340 km in MLT and the structures appeared to move eastward at 0.8 km s −1 . These scale sizes and eastward motion, along with the apparent rotation of the upward current sheets, are consistent with previous observations of auroral omega bands [ Opgenoorth et al , 1983; Wild et al , 2000, 2011]. These features are commonly seen toward the end of a substorm and our observations are consistent with this.…”
Section: Discussionsupporting
confidence: 93%
“…Before 0049 UT, Poynting flux had no significant variations (less than 0.01 mW/m 2 ), but it was obviously enhanced after 0049 UT, i.e., during the interval in which the eastward drifting FACs would pass over CL1. The peak value of the enhanced Poynting flux at CL1 exceeded 0.01 mW/m 2 , which was no more than the half of Poynting flux in the plasma sheet ∼8 R E tailward of the Earth [ Wild et al , 2011]. Just during the Poynting flux enhancements, the parallel and anti‐parallel electron DEFs were also slightly enhanced.…”
Section: Discussionmentioning
confidence: 99%
“…Their results suggested that the magnetospheric counterpart of omega bands/Ps6 pulsations originates from a localized region in the near‐Earth magnetotail. A recent study by Wild et al [2011] compared the ground‐based all‐sky imager measurements of omega bands with the in situ field and plasma measurements form the conjugate region in the near‐Earth magnetotail. Although they did not find a clear one‐to‐one correspondence between variations in the ionosphere and magnetosphere, they suggested that that Alfvén waves in the plasma sheet ∼8 R E tailward of the Earth are responsible for the generation of FACs that cause omega bands/Ps6 pulsations observed on the ground.…”
Section: Introductionmentioning
confidence: 99%